Fundos de pensão no Brasil: ferramentas de gestão e avaliação de riscos - Rezende, José Augusto da Silva (2010)
This dissertation brings a review on two management and risk assessment tools: VaR and Tracking Error and their applicability in pension funds. It describes the calculation methodologies and their employment in the management of a pension fund. It also reviews the literature on the employment of VaR and Tracking Error for risk assessment of pension funds. Consequently, make VaR and Tracking Error calculations for a theoretical pension funds portfolio, created from active principles and participations determined by the law. From this point on, it performs an exploratory study which seeks to analyze the tenure to a theoretical pension fund portfolio to a benchmark (inflation index composing the actuarial goal). For this purpose, six classes of financial assets were used such as stocks, interests and inflation risks. From these results, the work finds evidences that tenure assessment (Tracking Error), complemented by total risk Assessment, are useful tools for the management of pension funds and the findings on deviations of actuarial goals